A study on rumination and resting behaviour of osmanabadi kids housed in katcha housing system under different floor space (Indian Journal of Animal Production and Management, 2016)
The aim of this study was to evaluate the effect of different floor space on rumination and resting behaviour  of Osmanabadi kids. Eighteen Osmanabadi castrated kids with an initial average body weight (BW) of 6.80  kg at 3-4 months old age (after weaning) were used in this experiment. There were three different floor  space provision of 0.8, 0.7 and 0.6m2 in three experimental groups (T0, T1 and T2 respectively) with the  same managemental conditions. The behaviours were observed using continuous focal sampling method  and measured as minutes/4hr/week. The results indicated that the lying period under the category of  resting behaviour and rumination duration were significantly (P
Keywords: Floor space; Katcha housing; Osmanabadi kids; Resting behaviour; Rumination behaviour